POST-COMMUNIST EUROPEAN COUNTRIES IN GLOBAL VALUE CHAINS - Cieślik, Ewa (Ekonomika, 2014)
Transformations and integration processes of post-communist European states have resulted in changes in the production process across borders. The main objective of this article is to present the positions of post-communist states in terms of cross-border input–output linkages. The analysis takes advantage of both the conventional methods of comprehensive study of global value chains and the advanced methods and measures examining the role of Central and Eastern Europe in global value chains in general and in sectoral terms. Findings of the study suggest that more integrated are countries with grater connections to Western European countries, especially Germany; a large share of exported goods from the post-communist states passes through GVCs in Western Europe, and exporters from post-communist states are usually located more in downstream segments of production than in upstream markets.